Balanço econômico da operação de semeadura da cultura da soja em diferentes arranjos espaciais - Tavares, Leandro Augusto Felix [UNESP] (2015)
In an attempt to increase the financial return to farmers, researchers have studied diferente production methods such as the reduction of the spacing between rows during the sowing. However, a study of the economic balance is needed to know whether the use of this method at sowing is feasible for farmers. Therefore, the objective of this work was to evaluate the soybean crop as to the effect of different sowing systems using a precision and continuous flow seeder and as well as to evaluate the feasibility of these systems. The experiment was conducted in an experimental area from Fazendas de Ensino, Pesquisa e Extensão (FEPE) at Faculdade de Ciências Agronômicas from Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP), Botucatu campus. A randomized complete block design in a 4 [conventional seeding system (control), cross-seeding system, dense seeding system and seeding system in double row] x 2 (kind of seeder and fertilizer drill: precise and continuous flow) factorial arrangement with four repetitions in each treatment was used. The agricultural characteristics evaluated were plant height, string bean insertion, total plants counting, determination of water content in grains, determination of mass in 1,000 grains, and determination of productivity. The mechanical damage was also evaluated in seeds by the analyses of fast green test and germination test. Economic balance was found using the operating cost methodology of agricultural machines described by MIALHE (1974) and ASABE (2006). After conducted analysis of variance was verified statistical difference for all agronomic traits in the experiment. It is found that there were statistically significant differences in all agronomic traits in the experiment also is observed main types of seeder for the characteristics productivity and mechanical damage of soybean thus noted that the streaming seeder caused higher mechanical damage the seed of the sower of precision, so also was no statistical difference in the soybean yield, in that when the seeding was done with the precision seeder productivity was higher. Evaluating the spacing used in the study it was found that the spacing in double row obtained the highest production, differing from the other seeding arrangements. In relation to the total cost of production it was observed that the most costly seeding arrangements are that you must perform two passes in the same area, are these, crossed planting system with precision sowing machines, continuous flow, dense planting system with precision seeder. The benefit / cost of the systems it was found that the best seeding arrangement is the double row when the operation was carried out with a precision seeder.